UPAYA GURU BAHASA ARAB DALAM MENINGKATKAN MINAT BELAJAR BAHASA ARAB PESERTA DIDIK MADRASAH IBTIDAIYAH SWASTA (MIS) AL-BARKAH DESA CINTA RAKYAT, PERCUT SEI TUAN DELI SERDANG-SUMATERA UTARA - Muti Husnul Khotimah; Mirsa Triandani Siregar; Bella Tiara Putri (Jurnal Sathar, 2023)
Learning Arabic is very important in the world of Islamic education. In order to increase interest in learning Arabic among students in MIS Al-Barkah Cinta Rakyat Village, the efforts of the Arabic language teacher are needed during the learning process. During childhood, when they are at the elementary level, students really need more intense guidance from a teacher. The main problem studied is the learning interest of students in MIS Al-Barkah Cinta Rakyat Village, where the school environment is said to be unfamiliar with learning Arabic, so students are less interested in learning Arabic. This method uses a descriptive method with a qualitative approach. The data collection technique in the research is in the form of interviews with teachers in the field of Arabic studies, MIS Al-Barkah, Cinta Rakyat Village, and to make the data more effective the researcher collects literature in the form of journals, articles, and so on so that the research can be carried out. said to be accurate. The results that have been studied are the efforts of Arabic teachers to increase interest in learning Arabic among Mis Al-Barkah students, namely by means of a two-way interaction pattern, using audio-visual media, singing and reward methods